Maintenance of Effects and Correlates of Changes Following Mindfulness for Interdisciplinary Health Care Professional Students - Sarah Ellen Braun; Samantha N. Mladen; Christina M. Luberto; Patricia Anne Kinser (Mary Ann Liebert, 2022)
Objectives: To evaluate long-term outcomes after an 8-week mindfulness intervention, Mindfulness for Interdisciplinary Health Care Professionals (MIHP), and investigate relationships between outcomes overtime. Design/Methods: In this single-arm study, 35 participants received MIHP and completed measures of burnout, perceived stress, activity impairment, and dispositional mindfulness at baseline, post-MIHP, and a 3-month follow-up. Changes over time were evaluated using repeated-measures analysis of variance (ANOVA) and reliable change indices (RCIs). Then, correlations between dispositional mindfulness and distress/impairment outcomes were evaluated. Results: At follow-up, aspects of burnout and several mindfulness skills demonstrated maintained improvements. RCIs showed that a higher percentage of participants improved on all outcomes at each time period than declined?all outcomes showed little to no deterioration. However, most participants did not reliably change, and this was more pronounced at the follow-up. Changes in two mindfulness skills (acting with awareness and nonjudging of inner experience) were consistently negatively correlated with distress and impairment outcomes. Conclusions: Acquired mindfulness skills during MIHP were maintained at the follow-up. RCI analyses demonstrated that MIHP may protect against worsening stress and burnout during training. Two mindfulness skills, acting with awareness and nonjudging of inner experience, showed potential mechanistic effects on work-relevant outcomes. Booster sessions to encourage maintained mindfulness practices and skills should be investigated in future trials. This study was registered on clinicaltrials.gov (#NCT03403335) on January 11, 2018.